Next generation sequencing of SNPs using the HID-Ion AmpliSeq™ Identity Panel on the Ion Torrent PGM™ platform. (November 2016) - Guo, Fei; Zhou, Yishu; Song, He; Zhao, Jinling; Shen, Hongying; Zhao, Bin; Liu, Feng; Jiang, Xianhua
Highlights: Evaluation experiments demonstrate that the HID-Ion AmpliSeq™ Identity Panel is a well-performed, robust, reliable and high informative NGS-SNP assay. Some underperformed loci were identified including strand bias, low locus coverage, heterozygote imbalance and high background signals. Full profile could be obtained from as low as 100 pg input DNA. Compared with STR assays, this panel gives prominence to advantage on detection to degraded sample. FST across all 90 autosomal SNP loci showed no significant difference between Southern and Northern Chinese Han or between male and female samples. Forensic parameters for A-SNPs were calculated as >99.999% (CDP), 0.999999724 (CPE), 1.390 × 10 11 (CLR of trios) and 2.361 × 10 6 (CLR of duos). HD for Y-SNPs was equal to 0.684. Abstract: The HID-Ion AmpliSeq™ Identity Panel (the HID Identity Panel) is designed to detect 124-plex single nucleotide polymorphisms (SNPs) with next generation sequencing (NGS) technology on the Ion Torrent PGM™ platform, including 90 individual identification SNPs (IISNPs) on autosomal chromosomes and 34 lineage informative SNPs (LISNPs) on Y chromosome. In this study, we evaluated performance for the HID Identity Panel to provide a reference for NGS-SNP application, focusing on locus strand balance, locus coverage balance, heterozygote balance, and background signals. Besides, several experiments were carried out to find out improvements and limitations of this panel, including studies of species specificity, repeatability and concordance, sensitivity, mixtures, case-type samples and degraded samples, population genetics and pedigrees following the Scientific Working Group on DNA Analysis Methods (SWGDAM) guidelines. In addition, Southern and Northern Chinese Han were investigated to assess applicability of this panel. Results showed this panel led to cross-reactivity with primates to some extent but rarely with non-primate animals. Repeatable and concordant genotypes could be obtained in triplicate with one exception at rs7520386. Full profiles could be obtained from 100 pg input DNA, but the optimal input DNA would be 1 ng–200 pg with 21 initial PCR cycles. A sample with ≥20% minor contributor could be considered as a mixture by the number of homozygotes, and full profiles belonging to minor contributors could be detected between 9:1 and 1:9 mixtures with known reference profiles. Also, this assay could be used for case-type samples and degraded samples. For autosomal SNPs (A-SNPs), FST across all 90 loci was not significantly different between Southern and Northern Chinese Han or between male and female samples. All A-SNP loci were independent in Chinese Han population. Except for 18 loci with He <0.4, most of the A-SNPs in the HID Identity Panel presented high polymorphisms. Forensic parameters were calculated as >99.999% for combined discrimination power (CDP), 0.999999724 for combined power of exclusion (CPE), 1.390 × 10 11 for combined likelihood ratio (CLR) of trios, and 2.361 × 10 6 for CLR of motherless duos. For Y-SNPs, a total of 8 haplotypes were observed with the value of 0.684 for haplotype diversity. As a whole, the HID Identity Panel is a well-performed, robust, reliable and high informative NGS-SNP assay and it can fully meet requirements for individual identification and paternity testing in forensic science.